Solidaritas Sosial Pekerja Tetap PTPN VII Cinta Manis Kabupaten Ogan Ilir Sumatra Selatan - Istiqoma Istiqoma; Elita Aidillah; Adetia Wulindari; Akhmad Syafe’i; Decka Pratama Putra (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research examines the form and basis of organic social solidarity among permanent workers. Using a descriptive qualitative method, this research focuses on permanent workers who have organic social solidarity ties. workers who have organic social solidarity ties. Informants were selected purposive to obtain in-depth information, with 12 permanent workers and 2 key informants as research subjects. key informants as research subjects. Data collection techniques include observation, interviews, and documentation, with analysis using taxonomy techniques. taxonomy technique. The results showed that organic social solidarity at PTPN VII Sweet Love District is characterized by division of labor, fading collective consciousness, restitutive law, and interdependence. collective consciousness, restitutive law, and interdependence between parts. The basis of of this solidarity include work relatedness, membership in a labor union, class equality, and common hobbies. This research highlights the importance of in-depth understanding of the dynamics of social solidarity in the work environment.